Feasibility of home-based dietetic intervention to improve the nutritional status of older adults post-hospital discharge - Hamirudin, Aliza Haslinda; Walton, Karen; Charlton, Karen; Carrie, Amanda; Tapsell, Linda; Milosavljevic, Marianna; Pang, Glen; Potter, Jan (John Wiley & Sons, Inc., 2017)
Aim: To determine if a model of home-based dietetic care improves dietary intake and weight status in a specific group of older adults post-hospitalisation. Methods: The Department of Veterans’ Affairs clients aged 65 years and over were recruited from hospitals in a regional area of New South Wales, Australia (n = 32 men, n = 36 women). Nutritional status was assessed at home at baseline (within two weeks post-discharge) and three months post-discharge using a diet history, a food frequency checklist and Mini Nutritional Assessment (MNA). Personalised dietary advice was provided by a single dietitian according to participants’ nutritional status. Results: Mean body weight improved significantly (P = 0.048), as well as mean MNA score (21.9 ± 3.5 vs 25.2 ± 3.1) (P < 0.001). Mean energy, protein and micronutrient intakes were adequate at baseline and three months, except for vitamin D. At three months, the underweight group (body mass index (BMI) < 23 kg/m2) had significantly higher mean protein intake per body weight (1.7 ± 0.4 g/kg) compared to those who were a desirable weight (BMI 23–27 kg/m2) (1.4 ± 0.3 g/kg) or overweight (BMI>27 kg/m2) (1.1 ± 0.3 g/kg) peers (P < 0.001). There was significant improvement in energy intake contributed from oral nutrition supplements (+95.5 ± 388.2 kJ/day) and milk (+259.6 ± 659.8 kJ/day). Conclusions: Dietetic intervention improved nutritional status 3 months after hospital discharge in older adults living in the community.